Determinants of Corporate Social Responsibility in Listed Companies - Martin Gunawan (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The obligation of corporate social responsibility disclosure is growing up from Indonesian ordinance UU No. 40 Year 2007 as required for listed companies for philantrophy and as part of legitimacy act. Based on the requirements, this research conducted to determines empirically the hypothesis of factors that affect disclosure for companies listed in Stock Exchange in 2014 and 2015 using framework GRI G4 as disclosure measurement. The quantitative findings, using regression analysis test and data compliance in model classic assumption test for 22 listed company member of sustainability reporting, showed current ratio, debt to equity, size, institutional ownership and age have significant effects.